2007
DOI: 10.1111/j.1540-8159.2007.00926.x
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Verification of Ventricular Stimulation: Fusion Management Algorithm

Abstract: (PACE 2008; 31:64-69) automatic capture verification, back-up stimulation, evoked response, fusion phenomenon, intrinsic conduction search

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…ER underdetection is affected by various factors, such as increased polarization, low S/N ratio, or fusion/pseudofusion, and is reported to account for 0.5-1.4% of backup pacing 6,13,15 ; however, the recent implementation of fusion avoidance algorithms has enabled a portion of this unnecessary stimulation to be eliminated. 3,17 Among the 43 patients who had at least one missed detection of Vth during the 2-month study period, inadequate S/N ratio was found in 27 cases (4.7% of the sample). Some of these failures to measure Vth were associated with inadequate detection of ER, although this specific datum is not available: a nonnegligible portion of backup pacing in an acute setting may therefore be due to ER underdetection rather than a true threshold increase.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…ER underdetection is affected by various factors, such as increased polarization, low S/N ratio, or fusion/pseudofusion, and is reported to account for 0.5-1.4% of backup pacing 6,13,15 ; however, the recent implementation of fusion avoidance algorithms has enabled a portion of this unnecessary stimulation to be eliminated. 3,17 Among the 43 patients who had at least one missed detection of Vth during the 2-month study period, inadequate S/N ratio was found in 27 cases (4.7% of the sample). Some of these failures to measure Vth were associated with inadequate detection of ER, although this specific datum is not available: a nonnegligible portion of backup pacing in an acute setting may therefore be due to ER underdetection rather than a true threshold increase.…”
Section: Discussionmentioning
confidence: 98%
“…ER underdetection is affected by various factors, such as increased polarization, low S/N ratio, or fusion/pseudofusion, and is reported to account for 0.5–1.4% of backup pacing 6,13,15 ; however, the recent implementation of fusion avoidance algorithms has enabled a portion of this unnecessary stimulation to be eliminated 3,17 . Among the 43 patients who had at least one missed detection of Vth during the 2‐month study period, inadequate S/N ratio was found in 27 cases (4.7% of the sample).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the electrical delay may allow fusion/pseudofusion to occur, which in turn may confound special pacemaker functions, such as wasting battery due to repetitive pacing threshold tests or falsely counting intrinsic beats as ventricular paced events. 7 , 16 Thus, if a sensing delay is present, it needs to be carefully tailored to the individual AV delay. In point of fact, programming a longer AV delay, at least to the value of RV lead electrical delay, may encourage intrinsic ventricular activity.…”
Section: Discussionmentioning
confidence: 99%
“…This proof may raise important issues related to the management of intrinsic ventricular activity or the occurrence of ventricular fusion/pseudofusion, a common pitfall in device follow-up, as not only pacemakers but also cardioverter-defibrillators and devices for cardiac resynchronization therapy (CRT) use the RV lead itself for sensing. 7 , 8 Yet, basic knowledge regarding the relationship in time between QRS and acquired EGM from the RV lead is lacking in both narrow QRS and RBBB. One question of particular interest is the time at which RV lead sensing occurs at the mid-septum, which is nowadays considered the main alternative to the undesirable RV apical site for conventional pacemaker implantation.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive number of fusions in AT tests may result in prolonged tests, test failure, or inaccurate threshold measurement from fusion misclassifications 21–23 . There were questions regarding how fusion beats or premature ventricular contractions may affect the performance of the AT algorithm 24 .…”
Section: Fusion Managementmentioning
confidence: 99%